Changes in Intrathoracic Impedance are Associated With Subsequent Risk of Hospitalizations for Acute Decompensated Heart Failure: Clinical Utility of Implanted Device Monitoring Without a Patient Alert - Small, Roy S.; Wickemeyer, William; Germany, Robin; Hoppe, Bobbi; Andrulli, John; Brady, Peter A.; Labeau, Melody; Koehler, Jodi; Sarkar, Shantanu; Hettrick, Douglas A.; Tang, W.H. Wilson (Journal of cardiac failure, 2009)
Acute decreases in intrathoracic impedance monitoring have been shown to precede heart failure hospitalization in a limited population of heart failure patients. We evaluated the relationship between changes in intrathoracic impedance with hospitalizations associated with acute decompensated heart failure (ADHF) in patients with cardiac resynchronization therapy plus defibrillator (CRT-D) devices. The study enrolled 326 heart failure patients who had received CRT-D with impedance-monitoring capabilities (InSync Sentry, Medtronic). The date and duration of ADHF hospitalizations were retrospectively identified before device interrogation to obtain device diagnostic information. During 333 ± 96 days of device monitoring, 228 patients experienced 540 intrathoracic impedance fluid index threshold crossings events (TCE) at the nominal threshold value (60 Ω. days). During the initial 4-month evaluation period, 17 subjects experienced 22 ADHF hospitalizations. In the subsequent monitoring period (206 ± 95 days), 18 patients experienced 24 hospitalizations. The occurrence of TCEs during the monitoring period was independently correlated with the subsequent rate of ADHF hospitalization such that each TCE event during the risk stratification period was associated with a 35% increased risk for ADHF hospitalization in the remaining study period ( P = .001). Poisson regression indicated that the subgroup of patients with an annual average rate of more than 3 threshold crossings per year during the monitoring period were significantly more likely to be hospitalized for ADHF than those patients with no TCE during the monitoring period (0.76 [0.20–1.325] vs. 0.14 [0.05–0.23] hospitalizations/subject/y [95%CI]; P = .02). Likewise, Kaplan-Meier analysis revealed that subsets of patients with more than 3 TCEs per year or with more than 30 days per year above threshold during the risk stratification period had significantly higher rates of ADHF hospitalization during the post risk stratification period than subjects with no TCE events, respectively. In this multicenter retrospective cohort study, serial decreases in intrathoracic impedance sufficient to generate a fluid index threshold crossing as well as the net duration that the index remained above threshold during a 4-month monitoring period were associated with subsequent risk of ADHF hospitalization.